Compulsory voting, turnout, and support for left-wing parties: The case of Australia. (February 2023) - Held, Alexander
Abstract: Does compulsory voting and the higher voter turnout that it produces increase support for left-wing parties? An influential and highly cited study provides strong evidence for such an effect in Australia. However, several quasi-experimental studies find little support for it in Europe. Given these conflicting findings, this study reanalyzes the crucial Australian case. It uses a unique, more fine-grained district-level dataset (N=4, 219) and difference-in-differences designs to more directly test the assumed causal mechanism between compulsory voting and left-wing party support. Overall, it finds little evidence for the commonly assumed positive direct effect of turnout on Labor's vote share. Further analyses identify an indirect effect of turnout – Labor's decision to run candidates in more districts under compulsory voting – as an alternative mechanism and electoral system change and the Great Depression as potential confounding factors. These findings have important implications for our understanding of the political consequences of compulsory voting.